Mit einem Stabilisator dotiertes Polyethylen = Polyolefin doped with a stabilizer - Schuhen, Katrin; Enders, Markus (Espacenet, 2010)
The invention relates to a process for preparing a polyolefin doped with a stabilizer, preferably an antioxidant, wherein a polymerization of an olefin is performed in the presence of a stabilizer, preferably an antioxidant, and of a catalyst.